2012
DOI: 10.11144/javeriana.upsy11-4.uwdg
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Work: Developing a Gender- Responsive Approach for Girls in the Juvenile Justice System

Abstract: Este artículo revisa la prevalencia de niñas en el Sistema de Justicia Juvenil de Estados Unidos, compara las tasas de encarcelamiento nacional e internacional y examina las necesidades de un perfil de las niñas involucradas. Los autores ofrecen su modelo como ejemplo para desarrollar una aproximación dirigida al género femenino en el Sistema de Justicia, incluyendo una descripción de su operacionalización en una comunidad de los Estados Unidos. En los desarrollos críticos y la emergencia de oportunidades para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(20 reference statements)
0
11
1
Order By: Relevance
“…Researchers also ascribe great importance to the kind of environment in which programs should be delivered. To be responsive to females’ pathways into the justice system, a program environment should promote respect, empathy, safety, agency, and privacy (Bloom, 2003; Ravoira, Graziano, & Patino Lydia, 2012). These guidelines are supported by both qualitative and quantitative studies conducted with female samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also ascribe great importance to the kind of environment in which programs should be delivered. To be responsive to females’ pathways into the justice system, a program environment should promote respect, empathy, safety, agency, and privacy (Bloom, 2003; Ravoira, Graziano, & Patino Lydia, 2012). These guidelines are supported by both qualitative and quantitative studies conducted with female samples.…”
mentioning
confidence: 99%
“…Focus groups with at risk and delinquent girls in shelter care and in correctional facilities have also highlighted adolescent girls’ need to be respected, listened to, and taken seriously by caring counselors (Garcia & Lane, 2013). Justice-involved girls also believe that the most important skills for care workers to acquire include, the ability to listen to and communicate with them, relate to them, understand their problems, value their perspectives, and treat them with respect (Ravoira et al, 2012). Beyond such guidelines, however, most recent studies recognize that in designing intervention programs for females, it is still important to apply the core principles of evidence-based practice, as identified in the “what works” literature (Barnett, 2012; Hubbard & Matthews, 2008; Kerig & Schindler, 2013; Lanctôt, 2011; Moretti et al, 2010; Zahn et al, 2009).…”
mentioning
confidence: 99%
“…Some of these results are coincident with previous studies. For example, family traumas are more present in females than in males (Ravoira, et al, 2012). Although fewer girls than boys are involved in criminal behaviours, females present a worse profile than males do, with more complicated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although females are a minority in juvenile justice systems (Rhoades et al, 2016), different studies have shown a striking increase in the proportion of female youth involved in the criminal justice system over the last few decades (Bäckman et al, 2014;Pusch & Holtfreter, 2018;Puzzanchera & Adams, 2011;Snyder, 2008). While boys are more likely to be charged with violent offences (robbery and assault), female minor offenders are more likely to present status offences, such as incorrigibility, truancy, and running away (Johansson & Kempf-Leonard, 2009;Leve & Chamberlain, 2005;Pusch & Holtfreter, 2018;Ravoira et al, 2012). In addition, the likelihood of recidivism continues to be higher for boys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation